Evaluation of cabbage (Brassica oleracea L.Var.capitata) for Southern Kerala - Divya P (Department of Olericulture, College of Agriculture, 2013)
The experiment entitled “Evaluation of cabbage (Brassica oleracea L.var.capitata) for southern Kerala” was conducted at the Department of Olericulture, College of Agriculture, Vellayani, during 2012-2013. The objectives were to identify tropical cabbage varieties suitable for plains of southern Kerala and to study the influence of date of sowing on yield and quality. The experiment was laid out in the field in split plot design with four dates of sowing as main plot and 11 varieties of cabbage as sub plot treatments with five replications. Analysis of variance revealed significant difference among sowing dates, varieties and their interactions for all the characters studied. Among the four different sowing dates (October 1st, October 15th, November 1st and November 15th), November 1st sowing recorded best yield characters. Highest yield (net head weight) was recorded for November 1st sowing (519.03 g) followed by October 15th sowing (451.21 g). Sowing on November 1st resulted in early head formation and early head harvest. Better gross plant weight, non wrapper leaves per plant, leaf length, leaf breadth and leaf size were also observed in November 1st sowing. No significant differences were observed for head solidity, core length and quality characters like protein, vitamin A and vitamin C between different sowing dates. Least incidence of physiological disorders, pest and diseases were observed on November 1st sowing. Among the varieties, New Orient (645g) and NS 183 (614.83g) were the highest yielders. Head depth and head diameter were highest for NS 183 followed by New Orient. Earliest among the varieties was New Orient followed by NS 183 and the late variety was Red C-05. Significant differences were observed among varieties for all quality characters. Red C-05 had maximum protein (1.12%) and vitamin C (70.97 mg/100g).